Traumatic Events and Symptoms Among Mexican Deportees in a Border Community. Issue 1 (2nd January 2017) - Peña, Juan M.; Garcini, Luz M.; Gutierrez, Angela P.; Ulibarri, Monica D.; Klonoff, Elizabeth A.
ABSTRACT: Research on traumatic events experienced among Mexicans deported from the United States is scant. Using clinical interviews, this study assessed the frequency of traumatic events and symptoms of post-traumatic stress disorder (PTSD) among 47 Mexican deportees in a U.S.-Mexico border community. The majority of participants (98%) reported having experienced one or more traumatic events ( M = 9, SD = 5) and nearly half met DSM-IV-TR criteria for PTSD. Meeting criteria for PTSD was associated with a higher number of traumatic events. Results suggest that prevention, intervention, and policy efforts are necessary to improve the well-being of this understudied immigrant subgroup.